2006
DOI: 10.1021/bm060710i
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Fungal Poly(β,l-malic acid) and Poly(β,l-malate)s

Abstract: The thermal decomposition of poly(beta,l-malic acid), poly(alpha-methyl beta,l-malate), and ionic complexes of the polyacid with alkyltrimethylammonium salts was studied by TGA, GPC, and FTIR and NMR spectroscopy. It was found that poly(beta,l-malic acid) depolymerized above 200 degrees C by an unzipping mechanism with generation of fumaric acid which is then partially converted in a mixture of maleic acid and anhydride. On the contrary, random scission of the main chain was found to happen in the thermal deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Kinetic parameters resulting from this analysis are summarized in Table 2 showing that similar E values were obtained by both methods for the two polymers, which is in full agreement with the occurrence of a common degradation mechanism for the two polymers. It should be noted that the E values resulting in this study are of the same order as those reported for poly(malic acid) and poly(methyl b,L-malate) which were determined using the same thermogravimetric method [19]. …”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Kinetic parameters resulting from this analysis are summarized in Table 2 showing that similar E values were obtained by both methods for the two polymers, which is in full agreement with the occurrence of a common degradation mechanism for the two polymers. It should be noted that the E values resulting in this study are of the same order as those reported for poly(malic acid) and poly(methyl b,L-malate) which were determined using the same thermogravimetric method [19]. …”
Section: Resultssupporting
confidence: 66%
“…It is worthy mentioning that certain polyesters such as poly(caprolactone) [22] and poly(lactic acid) [23] are known to degrade also by such a type of mechanism with generation of caprolactone and lactide, respectively. Decomposition of poly(b,L-malic) and poly(methyl b,L-malate) is known to occur through unzipping depolymerisation too, although in this case the released products are mixtures of fumaric and maleic acids [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both onset and maximum rate decomposition temperatures are lower for the partially methylated products than for either of the two homopolymers. We reported recently on the thermal degradation of PMLA and PMLA-Me [17] showing that different decomposition mechanisms operate in each case. Decomposition of the polyacid takes place through an unzipping mechanism with the release of fumaric acid whereas the polymalate degrades by a random scission process leading to oligomeric fragments.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Portilla-Arias et al 114 reported that poly(b,L-malic acid) was depolymerized above 200 1C by an unzipping mechanism from chain ends with the generation of fumaric acid, which was secondary Materials and technologies for polymer recycling H Nishida converted into maleic acid and anhydride (Scheme 27). These aliphatic acids and anhydride are reused to be incorporated in many chemical products.…”
Section: Materials and Technologies For Polymer Recycling H Nishidamentioning
confidence: 99%